The internal realities of individuals with type 2 diabetes-Psychological disposition in self-management behaviour via grounded theory approach. - Yogarabindranath Swarna Nantha; Azriel Abisheg Paul Chelliah; Shamsul Haque; Anuar Zaini Md Zain (PLoS ONE)
Background A paradigm shift in the disease management of type 2 diabetes is urgently needed to stem the escalating trends seen worldwide. A "glucocentric" approach to diabetes management is no longer considered a viable option. Qualitative strategies have the potential to unearth the internal psychological attributes seen in people living with diabetes that are crucial to the sustenance of self-management behaviour. This study aims to identify and categorize the innate psychological dispositions seen in people with type 2 diabetes in relation to self-management behaviour. Methods We adopted a grounded theory approach to guide in-depth interviews of individuals with type 2 diabetes and healthcare professionals (HCP) at a regional primary care clinic in Malaysia. Twenty-four people with type 2 diabetes and 10 HCPs were recruited into the study to examine the inner narratives about disease management. Two focus group discussions (FGD) were also conducted for data triangulation. Results Participants' internal dialogue about the management of their disease is characterized by 2 major processes- 1) positive disposition and 2) negative disposition. Optimism, insight, and awareness are important positive values that influence T2D self-care practices. On the other hand, constructs such as stigma, worries, reservations, and pessimism connote negative dispositions that undermine the motivation to follow through disease management in individuals with type 2 diabetes. Conclusions We identified a contrasting spectrum of both constructive and undesirable behavioural factors that influence the 'internal environment' of people with type 2 diabetes. These results coincide with the constructs presented in other well-established health belief theories that could lead to novel behavioural change interventions. Furthermore, these findings allow the implementation of psychosocial changes that are in line with cultural sensitivities and societal norms seen in a specific community.